Do endoscopic features suggesting eosinophilic esophagitis represent histological eosinophilia?. Issue 2 (14th April 2013) - Hori, Kazutoshi; Watari, Jiro; Fukui, Hirokazu; Tanaka, Junji; Tomita, Toshihiko; Sakurai, Jun; Kondo, Takashi; Oshima, Tadayuki; Toyoshima, Fumihiko; Yamasaki, Takahisa; Okugawa, Takuya; Miwa, Hiroto
<x xml:space="preserve">Abstract</x> Background Esophageal linear furrows, corrugated rings, and/or white exudates are often seen in patients with eosinophilic esophagitis (EoE); however, whether these are specific to EoE remains unclear. Endoscopic surveillance of these features was conducted to determine whether these represent esophageal eosinophilia, which is essential for the diagnosis of EoE. Patients and Methods Two thousand seven hundred and sixty‐three patients were enrolled consecutively. Target biopsy was carried out when the above features were seen. Histological eosinophilia was defined as 24 or more eosinophils per high‐power field (HPF). Associations between features and eosinophilia were analyzed statistically. Results Two thousand five hundred and forty‐five patients completed the study. Linear furrows, corrugated rings and white exudates were seen in 24, 15 and 45 patients, respectively. These findings somewhat overlapped. Among 58 biopsied patients withany of the above features, these features represented eosinophilia in 14% (3/21), 23% (3/13), and 5% (2/43), respectively. None of the 199 patients who received biopsy for other features had eosinophilia. Two of five eosinophilia patients were diagnosed with EoE. Multiple comparisons revealed that eosinophil counts in linear furrows and corrugated rings but not white exudates were significantly greater than those in other features (12, 9, 1, and <1 eosinophils/HPF on average, respectively). Conclusions An endoscopic feature suggesting EoE does not always represent esophageal eosinophilia and is non‐specific for EoE, although it reminds endoscopists of the presence of EoE. The diagnostic utility of linear furrows or corrugated rings for esophageal eosinophilia is superior to that of white exudates.